Dampak Psikologis Pandemi COVID-19 Pada Mahasiswa - Ratunuman, Raldy A.; David, Lydia E. V.; Opod, Hendri (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: At the beginning of 2020 the world was surprised by the emergence of COVID-19 disease which was subsequently declared a pandemic by WHO in March 2020. This pandemic caused a global health crisis that impacted everyone. Campus life has also changed in response to the current pandemic, resulting in an impact on students' psychological condition. Aim: This study aims to find out what are the psychological impacts of the COVID-19 pandemic on students. This research was conducted in the form of review literature that is to explain and discuss it by taking materials from various available at ClinicalKey and PubMed based on inclusion and exclusion criteria. Eleven literatures were obtained, which from various countries. The age of the sample is 17-29 years. Female students with total 421,145 (55.7%) students. The psychological impacts found were anxiety, depression, stress, post-traumatic stress syndrome, and post-traumatic growth. Female students, volunteers, first year, residence, viral infection, and various other factors are associated with existing psychological symptoms. In conclusion, various psychological impacts experienced by students during the COVID-19 pandemic. The role of the government for the procurement and optimization of health programs is indispensable. Parents as expected can provide support.Keywords: psychological impact, COVID-19, university student Abstrak: Pada awal tahun 2020 dunia dikejutkan dengan munculnya penyakit COVID-19 yang selanjutnya dideklarasikan sebagai pandemi oleh WHO pada bulan Maret 2020. Pandemi ini menyebabkan krisis kesehatan global yang berdampak pada semua orang. Kehidupan kampus turut berubah menanggapi pandemi yang sedang terjadi, mengakibatkan dampak pada kondisi psikologis mahasiswa. Penelitian ini bertujuan untuk mengetahui apa saja dampak psikologis pandemi COVID-19 pada mahasiswa. Penelitian ini dilakukan dalam bentuk literatur review yaitu memaparkan dan membahasnya dengan mengambil bahan dari berbagai yang tersedia di pangkal data ClinicalKey dan PubMed berdasarkan kriteria inklusi dan eksklusi. Didapatkan sebanyak sebelas literatur yang sesuai, yang berasal dari berbagai negara. Usia sampel yaitu, 17-29 tahun. Mahasiswa perempuan sebanyak 421.145 (55.7%). Dampak psikologis yang ditemukan adalah kecemasan, depresi, stress, sindrom stress pasca trauma, dan pertumbuhan pasca trauma. Mahasiswa perempuan, relawan, tahun pertama, tempat tinggal, infeksi virus, dan berbagai faktor lain dikaitkan dengan gejala psikologis yang ada. Sebagai simpulan, Berbagai dampak psikologis yang dialami oleh mahasiswa yang dimasa pandemi COVID-19. Peran pemerintah untuk pengadaan dan optimalisasi program kesehatan sangat diperlukan. Orang tua sebagai diharapkan dapat memberikan dukungan.Kata kunci: dampak psikologis, COVID-19, mahasiswa